ANALYSIS OF THE EFFECTIVENESS OF THE TAḤFÎZ CLASS PROGRAM IN IMPROVING THE QUALITY OF AL-QUR'AN LEARNING OUTCOMES - Winda Seriyanti Putri; Syahida Rena; Muh. Ubaidillah Alghifary S (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to analyze the effectiveness of the tahfīẓ class program in improving the quality of Qur’anic learning outcomes among students at the elementary school level. The research focuses on how the program contributes to students’ memorization achievement, reading accuracy, learning attitudes, and practical recitation skills. A descriptive qualitative approach was employed to obtain an in-depth understanding of the program implementation and its learning outcomes. Data were collected through classroom observations, interviews with tahfīẓ teachers and school stakeholders, and documentation analysis. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the tahfīẓ class program is effective in enhancing students’ Qur’anic learning outcomes across cognitive, affective, and psychomotor domains. The use of structured instructional planning, consistent application of talaqqī and murāja‘ah methods, and continuous evaluation supported students’ memorization accuracy, discipline, and fluency in recitation. Additionally, parental involvement and a supportive learning environment played a significant role in sustaining learning consistency. Despite challenges related to students’ concentration and developmental characteristics, the program demonstrated strong potential as a holistic model for Qur’anic education in elementary schools.